Nanostructured ceramic materials: Applications in gas sensors and solid-oxide fuel cells - Lamas, Diego Germán (2010)
Two applications of nanostructured ceramic materials developed at CINSO in recent years are reviewed, including the synthesis and properties of these materials:(i)Application of nanostructured SnO2-based semiconductors for gas sensors, showing the increase of their sensitivity and the decrease of their operating temperature if the sensor is built with nanomaterials in comparison to sensors prepared with conventional microcrystalline materials. The sensing mechanism is discussed in order to explain the different behavior.(ii)Application of nanocrystalline ZrO2-CeO2 solid solutions as novel anodes for solid-oxide fuel cells operated using hydrocarbons as fuel. Other applications of nanoceramics in these devices, recently investigated at CINSO, are also discussed.